Synthesis of S-rich flower-like Fe2O3-MoS2 for Cr(VI) removal. Issue 11 (23rd July 2016) - Zhang, Ya; Chen, Peng; Wen, Fangfang; Meng, Yao; Yuan, Bo; Wang, Honggui
ABSTRACT: A novel Fe2 O3 -MoS2 nanocomposite was synthesized directly via the solvothermal method. Scanning electron microscopy (SEM) results showed the as-prepared Fe2 O3 -MoS2 had a uniform 3D blooming flower-like nanostructure with a MoS2 substrate. The high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) confirmed the Fe2 O3 nanostructures were well-dispersed on the surface of the layered MoS2 . The elemental mapping results revealed Fe, O, Mo and S elements coexisted in the Fe2 O3 -MoS2 nanocomposite. X-ray photoelectron spectroscopy (XPS) results displayed an S-rich MoS2 structure had been formed in the Fe2 O3 -MoS2 nanocomposite. As expected, the S-rich Fe2 O3 -MoS2 nanocomposite had better photocatalytic performance on Cr(VI) reduction than that of bare Fe2 O3, MoS2 and TiO2 P25.